MINAT BELAJAR DAN KEDISIPLINAN TERHADAP PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL - Dwi Sandira Putri (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2019)
The purpose of this study was to determine the effect of interest in learning and discipline together on learning achievement in Social Sciences, to determine the effect of interest in learning on learning achievement in Social Sciences, and to determine the effect of discipline on learning achievement in Social Sciences. The research sample was taken using proportional random sampling technique, with a total sample of 75 students from all seventh grade students of SMP Negeri in West Jakarta. Data collection was carried out by distributing questionnaires and learning achievement tests. Data analysis consisted of testing research instruments with validity and reliability testing. Furthermore, the analysis requirements test was carried out with the normality test and the homogeneity test. Hypothesis testing is done using multiple linear regression. This research was conducted from October 2019 to January 2020. Based on the results of the hypothesis and data analysis, the following concludes: 1) There is a significant influence on learning interest and discipline together on the learning achievement of students of State Junior High Schools in Jakarta West. This is evidenced by Sig = 0.000 <0.05 and Fcount = 9.400. 2) There is a significant effect of interest in learning on the learning achievement of Social Science students of SMP Negeri in West Jakarta. This is evidenced by Sig = 0.002 <0.05 and tcount = 3.205. 3) There is a significant effect of discipline on the learning achievement of Social Science students of SMP Negeri in West Jakarta. This is evidenced by Sig 0.027 <0.05 and tcount = 2.265